The Effect of Liquidity, Profitability and Solvency on Stock Returns In Manufacturing Companies Listed on The Indonesia Stock Exchange For The 2016-2020 Period - Nugraha, Aldi Satya; Karyatun, Subur; Digdowiseiso , Kumba (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
This study aims to analyze the effect of Liquidity, Profitability, and Solvability of Stock Return on Manufacturing Companies for the 2016-2020 Period. The data in this study uses secondary data in the form of financial statements that meet the criteria. Data from financial statements obtained from the official website of the Indonesia Stock Exchange which can be accessed through www.idx.co.id. The technique used in the analysis in this study is a linear regression of panel data using the Eviews 10 program. The results of this study show that Liquidity has a positive and significant effect on stock returns, Profitability has a negative and insignificant effect on stock returns, and Solvency does not affect stock returns.